1977
DOI: 10.1111/j.1744-6570.1977.tb02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Employment Test Validation for Minority and Nonminority Production Workers

Abstract: The purposes of the present study were (a) to examine the validity of selected employment tests potentially useful in selecting production workers engaged in the construction of boxboard containers and (b) to evaluate the applicability of the tests to minority and non‐minority workers. Using data collected from 100 production workers employed by the same company but located in two different geographical regions, it was found that a short test battery was potentially useful in selecting production employees wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In this model minority status and sex are included in predictive analyses along with other relevant variables to determine their unique contribution to explaining criterion variance. Consistent with a growing body of literature which suggests that minority status and sex are seldom important factors in employment decisions (Field, Bayley, and Bayley, 1977;Distefano, Pryer, and Craig, 1976), no "correction factors" were found to be warranted for the occupational groups included in this study.…”
Section: Discussionsupporting
confidence: 72%
“…In this model minority status and sex are included in predictive analyses along with other relevant variables to determine their unique contribution to explaining criterion variance. Consistent with a growing body of literature which suggests that minority status and sex are seldom important factors in employment decisions (Field, Bayley, and Bayley, 1977;Distefano, Pryer, and Craig, 1976), no "correction factors" were found to be warranted for the occupational groups included in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Although it has been found that the slopes of both the Black and White regression lines are often similar, they frequently have different intercepts (e.g. Boehm, 1977;Field, Bayley, & Bayley, 1977;Gael, Grant, & Ritchie, 1975b;Grant & Bray, 1970;Schmidt, Berner, & Hunter, 1973). Furthermore, the intercept of the regression line for Blacks is frequently found to be lower than that for Whites, indicating that the use of a common regression line would over-predict job performance for Blacks according to the Cleary rule.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…Studies used to assess differential prediction normally use a combination of ability tests, including not only cognitive ability, but also knowledge and special skills such as clerical speed and accuracy (e.g. Boehm, 1977;Field et al, 1977;Gael et al, 1975b;Grant & Bray, 1970;Schmidt et al, 1973). Therefore, these differential prediction studies cannot necessarily be generalized to characterize CATs exclusively.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…Studies used to assess differential prediction normally use a combination of ability tests, including not only cognitive ability but knowledge and special skills such as clerical speed and accuracy (c.f., Boehm, 1977;Field, Bayley & Bayley, 1977;Grant & Bray, 1970;Gael, Grant & Ritchie, 1975b;Schmidt, Berner & Hunter, 1973). Therefore, these differential prediction studies cannot necessarily be generalized to characterize CATs exclusively.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…The assumption, however, is that both Blacks and Whites are characterized by the same regression line. Although it has been found that the slopes of both the Black and White regression lines are often similar, they frequently have different intercepts (e.g., Boehm, 1977;Field, Bayley & Bayley, 1977;Grant & Bray, 1970;Gael, Grant & Ritchie, 1975b;Ruch, 1972, as cited in Arvey & Faley, 1988;Schmidt, Berner & Hunter, 1973). Furthermore, the intercept of the regression line for Blacks is frequently found to be lower than the regression line for Whites, indicating that the use of a common regression line would over-predict job performance for Blacks according to the Cleary rule.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%